Experimental Mathematics. Volume 16, Number 3, 2007 - A K Peters (A K Peters, 2009)
Hypergeometric Forms for Ising-Class Integrals Full TextPDF (335.9 KB) Authors D. H. Bailey, D. Borwein, J. M. Borwein and R. E. Crandall 257-276 No access to content Tropical Polytopes and Cellular Resolutions Full TextPDF (317.5 KB) Authors Mike Develin and Josephine Yu 277-291 No access to content Jointly Periodic Points in Cellular Automata: Computer Explorations and Conjectures Full TextPDF (212.4 KB) Authors Mike Boyle and Bryant Lee 293-302 No access to content Finding All Elliptic Curves with Good Reduction Outside a Given Set of Primes Full TextPDF (260.7 KB) Authors J. E. Cremona and M. P. Lingham 303-312 No access to content The D4 Root System Is Not Universally Optimal Full TextPDF (215.1 KB) Authors Henry Cohn, John H. Conway, Noam D. Elkies and Abhinav Kumar 313-320 No access to content Schwarz Reflection Geometry II: Local and Global Behavior of the Exponential Map Full TextPDF (5.6 MB) Authors Annalisa Calini and Joel Langer 321-346 No access to content On the Efficiency of the Simple Groups of Order Less Than a Million and Their Covers Full TextPDF (223.1 KB) Authors Colin M. Campbell, George Havas, Colin Ramsay and Edmund F. Robertson 347-358 No access to content On the Integral Carathéodory Property Full TextPDF (165.8 KB) Author Winfried Bruns 359-365 No access to content Equality of Polynomial and Field Discriminants Full TextPDF (220.1 KB) Authors Avner Ash, Jos Brakenhoff and Theodore Zarrabi 367-374 No access to content A Hardy–Ramanujan Formula for Lie Algebras Full TextPDF (501.2 KB) Author Gordon Ritter